Struggle Of Classes In Thackeray's Vanity Fair: A Marxist Approach - Hartatik., Sri (2004)
The object of the research is the novel entitled Vanity Fair (1848) by William Makepeace Thackeray. The study gives focus on Thackeray's view on the struggle of major character, Rebecca (lower class) to get high strata position. The study aims at studying Thackeray's view on Rebecca's struggle. The writer uses qualitative method in conducting the study. The primary data is the novel itself. The secondary data are the references, such as: the author's biography, essays, comments, and other relevant information which support the subject matter. The data collecting technique is documentation and library research, while the data analyzing technique is descriptive and hermeneutics. The witer uses Marxist theory as a means of analysis. The outcome of this study shows that: firstly, the structural elements of this novel present a unity. William Makepeace Thackeray employs the traditional plot that represents exposition, complication, climax and resolution. He takes the gap between upper and lower class which must be ended as his theme. The characters in Vanity Fair consist of two opposing characters that are represented by the upper class and the lower class.Secondly, Thackeray's view that the lower class struggle like Becky's struggle is needed. When the lower class feel injustice or unequal they have to struggle in order to get equal moreover if the struggle uses right way, so it will be more valuable.